An inventory of The Personal and Social Competences of School Counsellor Candidates - Nur Afriany Syarifuddin; Abdullah Sinring (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2020)
The purpose of this study is:  1) To find out the overview level of needs for school counsellor's competencies Inventory 2) Develop a competency inventory of BK teacher candidates that is valid, reliable and practical to be used for BK teacher candidates. This research is a research and development model of Borg and Gall by involving 20 prospective BK teachers. The results show that 1) The social competencies of the school counsellor's inventory as an instrument was needed by school counsellors candidates because inventory needed updating in terms of form, content and problem areas as well as statement items by the competencies measured in the Teacher Competency Examination (UKG) assessment. 2) Inventory of social personality competencies of BK teacher candidates developed following the objectives to be achieved because researchers have gone through trial steps in developing an inventory of social personality competencies for BK teacher candidates. The instrument validity value with valid criteria and the reliability test value is in the very reliable category based on the results obtained. As for the school counsellor's practicality test, it was obtained within the practical criteria. So it can be concluded that the inventory with a total of 115 statement declared valid, reliable, and prophecy can be used as an inventory of BK personal candidates' social personality competencies.